Unlocking relief: Lower half laminectomy for lumbar disc herniation under spinal anesthesia: An institutional perspective - Jiwesh Kumar; Kaushik Roy; Krishnendu Sardar; Anita Singh (Ukrainian Neurosurgical Journal)
Lumbar disc herniation is a prevalent spinal condition characterized by the displacement of intervertebral disc material leading to back pain and neuropathies. Surgical intervention, including decompressive laminectomy, is often recommended for patients who fail to respond to conservative treatment. The procedure of unilateral or bilateral lower half laminectomy, with or without disc herniation removal, has been described as an effective surgical technique for treating lumbar disc herniations. Purpose: The aim of the study was the assessment of outcomes including complications in patients undergoing limited laminectomy with discectomy. Material and methods: A total of 188 patients over a period from May 2022 till May 2024 were prospectively studied.Outcomes were assessed using Odom’s criteria, including complication, recovery status at subsequent follow up at 1 and 3 months. Results: Out of 188 patients, single disc herniations were seen in 155 while 2-level disc were seen in 33 cases. Among these, L5-S1 level herniation was most common , and in multi-disc herniation, L5-L5,L5-S1 levels were common. Most patients presented with radicular pain(127) followed by motor deficits or sensory deficits. Post operative recovery status was classified as excellent in the majority of cases (121 out of 188) with very less in fair and none in poor category. The recovery was gradually towards better grades in subsequent follow-ups. Duration of surgery was less than 1 hour in about 90% cases (16 out of 188). Conclusions: All cases were done under spinal anaesthesia. Adequate surgical exposure was obtained. The technique allowed for early mobilization, reduced hospital stay apart from a shorter learning curve requirement as compared to microscopic or endoscopic procedures. During discectomy the thickened ligamentum flavum (causing canal stenosis/narrowing) can also be dealt in single procedure. This procedure could be a safer alternative to the newer modalities of minimally invasive surgeries for lumbar decompression.